Pengaruh Merdeka Belajar Pendidikan Agama Kristen dan Budi Perkerti Terhadap Keaktifan Belajar Siswa Kelas IV SD Negeri 14 Tanjungan Kecamatan Simanindo Kabupaten Samosir Tahun Ajaran 2023/2024 - Herlin Utari Simorangkir; Sudirman Lase; Rida Gultom; Pestaria Naibaho; Tianggur Medi Napitupulu (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The research aims to determine the effect of independent learning on the learning activity of class IV students at SD Negeri 14 Tanjungan, Simanindo District, Samosir Regency. The research hypothesis is that there is a positive influence between independent learning in Christian Religious Education and Characteristics on the active learning of class IV students at SD Negeri 14 Tanjungan, Simanindo District, Samosir Regency, Academic Year 2023/2024. This research method is descriptive quantitative. The population of all class IV students at SD Negeri 14 Tanjungan for the 2023/2024 academic year is 35 people. The sampling is the entire population so this research is population research. The research instrument is a closed questionnaire. The results of the analysis requirements obtained a value of rxy=0.476>rtable=0.334 indicating that there is a positive relationship between freedom to learn Christian Religious Education and Character and student learning activeness. Regression test results obtained: a) Regression equation. b) The determination test showed that the percentage of independent learning influence of Christian Religious Education and Character on the active learning of class IV students at SD Negeri 14 Tanjungan was 22.66%. Hypothesis testing obtained Fcount=12.152>Ftable=3.32, so H0 is rejected and Ha is accepted. The research concluded that there was a positive influence between independent learning in Christian Religious Education and Characteristics on the active learning of class IV students at SD Negeri 14 Tanjungan, Simanindo District, Samosir Regency, Academic Year 2023/2024.